2014
DOI: 10.1177/0961203313518624
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of the factors associated with damage in Malaysian patients with lupus nephritis

Abstract: Higher maximum daily prednisolone dose predicted disease damage whereas treatment with early HCQ and early CR had a protective role against disease damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
(54 reference statements)
0
25
1
Order By: Relevance
“…On the other hand, the Pakistani lupus study showed higher renal damage of 37.5% [21]. The discrepancies can be explained by other various factors such as different treatment protocol and a wide spectrum of different histological renal changes which have influence in determining the outcome of LN [35,36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Pakistani lupus study showed higher renal damage of 37.5% [21]. The discrepancies can be explained by other various factors such as different treatment protocol and a wide spectrum of different histological renal changes which have influence in determining the outcome of LN [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Antimalarial agents have been used to treat SLE in over 50 years and since 1990s, there is well-established evidence of its various benefits including anti-thrombotic, anti-hyperlipidaemic, prevention of disease flares and damage in lupus [38]. Our previous studies have also found that the use of HCQ was associated with less disease damage in a small lupus nephritis cohort [35] and was associated with less SDM complication [45]. …”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine has been recognized to be an important immunomodulator treatment that potentially protects against disease damage complicated by the underlying disease or CS treatment . The use of HCQ was demonstrated to be associated with a significantly lower mean serum glucose level among the Baltimore lupus cohort participants, as well as protective effect against abnormal glucose tolerance .…”
Section: Discussionmentioning
confidence: 99%
“…Disease activity, corticosteroids and immunosuppressive therapy, all contribute to future damage. Cumulative disease activity over years is the single best predictor of damage across all age groups . Certain disease manifestations like renal and neuropsychiatric involvement predict higher damage accrual over time .…”
Section: Damage In Childhood Onset Lupusmentioning
confidence: 99%
“…Certain disease manifestations like renal and neuropsychiatric involvement predict higher damage accrual over time . Other important risk factors for damage are presence of anti‐phospholipid antibodies and acute thrombocytopenia . Therapy‐related damage is maximally contributed by high‐dose corticosteroid therapy in children .…”
Section: Damage In Childhood Onset Lupusmentioning
confidence: 99%